2017
DOI: 10.3748/wjg.v23.i39.7110
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term results of endoscopic ultrasound-guided transmural drainage for pancreatic pseudocysts and walled-off necrosis

Abstract: AIMTo evaluate the short- and long-term results of endoscopic ultrasound-guided transmural drainage (EUS-GTD) for pancreatic fluid collection (PFC) and identify the predictive factors of treatment outcome for walled-off necrosis (WON) managed by EUS-GTD alone.METHODSWe investigated 103 consecutive patients with PFC who underwent EUS-GTD between September 1999 and August 2015. Patients were divided into four groups as follows: WON (n = 40), pancreatic pseudocyst (PPC; n = 11), chronic pseudocyst (n = 33), and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
(30 reference statements)
1
26
1
Order By: Relevance
“…However, based on all data from relevant studies, the risk of recurrence was similar for the LAMS, FCSEMS, and DPPS. According to recent studies, the strongest risk factors for recurrence were identified as PFC occurring from chronic pancreatitis and disconnected pancreatic duct syndrome (DPDS), but not stent type . The likelihood of PFC recurrence with underlying chronic pancreatitis might be attributed to the presence of multifocal main pancreatic duct stricture and multiple pancreatic duct stones and thus an increased risk of intraductal obstruction .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, based on all data from relevant studies, the risk of recurrence was similar for the LAMS, FCSEMS, and DPPS. According to recent studies, the strongest risk factors for recurrence were identified as PFC occurring from chronic pancreatitis and disconnected pancreatic duct syndrome (DPDS), but not stent type . The likelihood of PFC recurrence with underlying chronic pancreatitis might be attributed to the presence of multifocal main pancreatic duct stricture and multiple pancreatic duct stones and thus an increased risk of intraductal obstruction .…”
Section: Discussionsupporting
confidence: 91%
“…According to recent studies, the strongest risk factors for recurrence were identified as PFC occurring from chronic pancreatitis and disconnected pancreatic duct syndrome (DPDS), but not stent type . The likelihood of PFC recurrence with underlying chronic pancreatitis might be attributed to the presence of multifocal main pancreatic duct stricture and multiple pancreatic duct stones and thus an increased risk of intraductal obstruction . Furthermore, the DPDS, which is characterized by main pancreatic duct discontinuity in association with a persistent nonhealing pancreatic fistula or PFC, could lead to a persistent leakage of pancreatic juice to PFC .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be helpful to identify predictive parameters associated with the need for repeated DEN, since this is the patient group that will probably have the greatest benefit from therapy with LAMS. Factors that were predictive for the need for DEN in previous studies were a larger size of the WON with more necrotic debris [18,19], while the amylase level in the cavity was associated with recurrence of PFC [19]. In our analysis, we could not confirm an association between the size of the PFC (as measured by EUS) and treatment time or number of follow-up endoscopic sessions.…”
Section: Discussioncontrasting
confidence: 72%
“…We speculated this was related to the higher mean proportion of solid debris roughly calculated by CT in infection group (32%) than non-infection group (15%). Watanabe et al also proposed that patients with WON with a high proportion of necrotic tissue had lower treatment success rate 36 . Although we found no statistical difference in postoperative infection between WON and PPC, the summary of RR on the postoperative infection may indicate that the potential risk in WON (9%) was 1.57 times (95%CI: 0.73-3.39) higher than PPC (2%).…”
Section: Discussionmentioning
confidence: 99%